Cardioprotective efficacy against reperfusion injury of EMD-87580: Comparison to ischemic postconditioning - Fantinelli, Juliana Catalina (2014)
Previous results show that prolonged treatment with EMD-87580 (EMD) NHE-1 blocker attenuates and reverses postinfarction remodelling. Our aim was to evaluate the effects of the treatment of EMD compared to ischemic postconditioning (IPO) in a model of regional ischemia. Isolated hearts were subjected to 40-min coronary occlusion followed by 60-min reperfusion (IC). Other hearts were treated with EMD 5 μM during the first 10 min of reperfusion or submitted to one cycle of 2 min of reperfusion and 2 min of ischemia as IPO protocol. Infarct sizes (IS), postischemic myocardial and vascular functions were assessed. The concentration of thiobarbituric reactive substances (TBARS), reduced glutathione (GSH) and expression of phosphorylated forms of ERK1/2, Akt, GSK-3β, eNOS were analyzed. MnSOD cytosolic activity – as an index of mitochondrial permeability – was also measured. EMD treatment and IPO decreased IS 50% and significantly improved the postischemic recovery of contractility and coronary perfusion. TBARS decreased and GSH increased after interventions compared to the values observed in IC hearts. MnSOD cytosolic activity increased in IC group and was significantly attenuated by EMD and abolished in IPO hearts. The content of P-ERK1/2 increased whereas P-Akt, P-GSK-3β and P-eNOS decreased in IC hearts. EMD treatment and IPO reversed these changes. The present data show that EMD treatment at the beginning of reperfusion-similarly to IPO- limited infarct size and attenuated the postischemic impairment of myocardial function through reactive oxygen species-mediated ERK1/2/Akt/GSK-3β/eNOS pathways